Glycan Microarray-Assisted Identification of IgG Subclass Targets in Schistosomiasis - Yang, Y. Y. Michelle; van Diepen, Angela; Brzezicka, Katarzyna; Reichardt, Niels-Christian; Hokke, Cornelis H. (Frontiers in Immunology, 2018)
Infection with schistosomes is accompanied by the induction of antibodies against the parasite. Despite having IgG against both protein and glycan antigens, infected individuals remain chronically infected for many years, or until treated, and re-infection is common in endemic areas due as immunity does not develop effectively. Parasite specific IgG subclasses may differ in functionality and effectivity with respect to effector functions that contribute to parasite killing and immunity. In this study, we investigated if specific IgG subclasses target specific antigenic schistosome glycan motifs during human infection. Sera from 41 S. mansoni infected individuals from an endemic area in Uganda were incubated on two glycan microarrays, one consisting of a large repertoire of schistosome glycoprotein- and glycolipid- derived glycans and the other consisting of chemically synthesized core xylosylated and fucosylated N-glycans also expressed by schistosomes. Our results show that highly antigenic glycan motifs, such as multi-fucosylated terminal GalNAc(β1-4)GlcNAc (LDN) can be recognized by all IgG subclasses of infection sera, however with highly variable intensities. Detailed examination of core-modified N-glycan targets revealed individual antibody responses specific for core-xylosylated and core α3-fucosylated motifs that are life stage specifically expressed by schistosomes. IgG1 and IgG3 were detected against a range of N-glycan core structures, but IgG2 and IgG4, when present, were specific for the core α3-fucose and xylose motifs that were previously found to be IgE targets in schistosomiasis, and in allergies. This study is the first to address IgG subclass responses to defined helminth glycans.